The Effect of the Leaven Against to Quality of Banana Kepok (Musa paradisiaca L) Tapai - wiwik Gusnita; Kasmita Kasmita (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Banana (Musa paradisiaca normalis linn) is a type of tropical fruit that is very popular, because of it is tastes good, is easy to get and the price is relatively cheap, bananas also contain vitamins, minerals and carbohydrates which are quite high. Society in general consumes bananas as a dessert. Therefore, in the context of developing food diversification, processed banana products can overcome the saturation of fresh bananas and increase their shelf life and increase their economic value. Bananas can be processed into various processed products such as dry banana, banana flour, banana jam, banana wine, banana tapai, and banana sauce. Among the processed banana products, fermentation processing that is making banana tapai is an alternative that is not yet well known to the public, but has a pretty good future. The purpose of this study was to analyze the effect of giving different amounts of leaven and to analyze the right amount of leaven in making Kepok banana tapai. This type of research is an experiment with panelist data sources using organoleptic tests. Based on the results of experiments with 4 (four) treatments and 4 (four) quality repetitions which resulted in the color produced from tapai banana kepok is yellowish white the best results in the third treatment (0.35), the aroma of tapai banana produced is typical scented tapai Banana Kepok the best results in the third treatment (0.35% leaven), taste Banana Kepok tapai produced, sweet and taste leaven, the best results in the third treatment (0.35% leaven), and texture of Kepok banana tapai produced was the best soft yield at the third treatment (0.35% leaven).